Comparing of Metaphoric Expressions Comprehension between Hearing Impaired Students and Normal Students of Junior High School - Reyhaneh Mohammadi; Tahereh Sima-Shirazi; Reza Nili-Pour; Mahdi Rahgozar; Abbas Pourshahbaz (University of Social Welfare and Rehabilitation Sciences, 2010)
Objective: Hearing impairment is the most common disability in birth. Many hearing impaired people suffer from language impairment such as metaphor comprehension. The purpose of this study is comparison of comprehension of metaphoric expressions in normal students with hearing impaired of junior high school sever. Materials & Methods: In this descriptive-analytic and comparative research, fifty hearing students and twenty five hearing impaired students were selected in a simple random sampling from normal and exceptional schools. Two researcher- made tasks have been used. At first the content validity and then with test re test reliability of non metaphoric words (r=0.724) and metaphoric expression comprehension task were determined. Then task of non metaphoric words was performed. If the subjects answered more than 75 percent of words correctly and they had all of inclusion criteria, task of metaphoric expression comprehension task was performed. Data were analyzed by statistical test such as independent sample T test and one way ANOVA. Results: There was significant difference in score of comprehension of metaphoric expressions between two groups (P<0. 001). The most number of incorrect answers of hearing impaired students were literal. In both groups, there was no significant difference in mean score of comprehension of metaphoric expressions between three grades of junior high school. Conclusion: Hearing impaired students had no development in comprehension of metaphoric expressions in first, second and third grade of junior high school and they understand metaphoric expressions literally according to their incorrect answers. They need especial training because of their significant different with hearing students.